Application of ARDRA and PLFA analysis in characterizing the bacterial communities of the food, gut and excrement of saprophagous larvae of Penthetria holosericea (Diptera: Bibionidae): a pilot study - Oravecz, O; Elhottová, D; Kristůfek, V; Sustr, V; Frouz, J; Tríska, J; Márialigeti, K (Folia microbiologica, 2004)
Amplified ribosomal DNA restriction analysis (ARDRA) was used to compare the bacterial communities of the food, the gut sections (ceca, anterior and posterior midgut, hindgut) and the excrement of the litter feeding bibionid larvae of Penthetria holosericea. For universal eubacterial primers ARDRA patterns were complex with only minor differences among samples. Taxon specific primers were also applied to characterize the samples. Fragment composition was transformed to presence/absence binary data and further analyzed. Cluster analysis revealed that bacterial communities of gut highly resembled each other with the exception of the ceca. ARDRA patterns of consumed leaves clustered together with the intact leaves but differed from those of the excrement. ARDRA results were compared with microbial community structure based on phospholipid fatty acid (PLFA) fingerprints. The cluster analysis of PLFA (presence/absence binary) data resulted in a pattern similar to the ARDRA data. The PCA analysis of PLFA relative content separated microbial communities into five groups: (1) anterior and posterior midgut, (2) hindgut, (3) ceca, (4) consumed and intact litter, (5) excrement. Both methods indicated that conditions in the larval gut result in formation of a specific microbial community which differs from both the food and excrement ones. Particularly ceca--(blind appendages, harbor very specific microbial community) are divided from the rest of the gut by perithropic membrane.
Keywords: Feces; střeva; Cluster Analysis; Animal Feed; mastné kyseliny; Bacteria; cékum; shluková analýza; DNA fingerprinting; DNA Fingerprinting; Fatty Acids; krmivo pro zvířata; Cecum; larva; Animals; Phospholipids; zvířata; fosfolipidy; polymorfismus délky restrikčních fragmentů; Larva; Intestines; Diptera; feces; Polymorphism, Restriction Fragment Length